2017
DOI: 10.17554/j.issn.2224-3992.2017.06.739
|View full text |Cite
|
Sign up to set email alerts
|

Similarities in Hepatitis C Patient Profiles Over a Decade in an Urban GI Clinic

Abstract: INTRODUCTION: There is considerable uncertainty with respect to predicting the liver disease status of African American (AA) patients with Hepatitis C seen in the current era of highly effective direct acting anti-virals (DAA). This uncertainty is due to the complex interplay between the identification of patients early in their disease progression by screening, the fact that many AA patients failed earlier interferon based therapy, duration of the HCV viremia in AA patients, the possible variation In disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
2
2
0
Order By: Relevance
“…1-4 While the number of treated patients has increased, the number of untreated, infected patients continues to be significant. [5][6][7][8][9][10][11][12][13] A study of predominantly African American (AA) patients in our university medical practice, during the interferon era (2002)(2003) and prior to the introduction of DAAs (2012-2013), confirmed that the AA population was within the age cohort for our patients through 2013. 5 While this aging cohort has traditionally represented the bulk of patients with HCV, the possibility that younger patients will be identified in recent populations is an important area of investigation.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…1-4 While the number of treated patients has increased, the number of untreated, infected patients continues to be significant. [5][6][7][8][9][10][11][12][13] A study of predominantly African American (AA) patients in our university medical practice, during the interferon era (2002)(2003) and prior to the introduction of DAAs (2012-2013), confirmed that the AA population was within the age cohort for our patients through 2013. 5 While this aging cohort has traditionally represented the bulk of patients with HCV, the possibility that younger patients will be identified in recent populations is an important area of investigation.…”
Section: Introductionsupporting
confidence: 58%
“…[5][6][7][8][9][10][11][12][13] A study of predominantly African American (AA) patients in our university medical practice, during the interferon era (2002)(2003) and prior to the introduction of DAAs (2012-2013), confirmed that the AA population was within the age cohort for our patients through 2013. 5 While this aging cohort has traditionally represented the bulk of patients with HCV, the possibility that younger patients will be identified in recent populations is an important area of investigation. 6 New infections with HCV continue to occur in the United States, with an estimated 2.4million Americans living with HCV in 2018.…”
Section: Introductionsupporting
confidence: 58%
“…While there are publications describing patients in each era, few address patients seen in the same clinical setting in two eras [19][20][21][22][23], and none that report on patients seen 17 years apart. Observations from these studies demonstrate an overall aging of the population along with an increase in the percentage of younger patients in the DAA era.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic Hepatitis C CHC) affects 2.4 million people in the United States and is one of the leading causes of cirrhosis, hepatocellular carcinoma and liver transplantation [1][2][3][4] . African Americans (AA) who are more likely to be infected with hepatitis C than Caucasians, comprise 23% of infected population, are more likely to develop hepatocellular carcinoma than non-AA populations in the United States, and are more likely to be infected with hepatitis C genotype [5][6][7][8][9][10] . Ribavirin/Interferon based regimens were less effective in the African American population which helped to contribute to the increased numbers of AA patients with CHC [11][12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%